Multichannel Long-Range Surface Plasmon Waveguides for Parallel Biosensing - Wong, Wei Ru; Fan, Hui; Adikan, Faisal Rafiq Mahamd; Berini, Pierre (Institute of Electrical and Electronics Engineers, 2018)
Two multichannel long-range surface plasmon waveguide structures are presented for parallel biosensing applications. The required ancillary passive optical elements are modeled and validated via comparisons with measurements to find good designs for the multichannel structures. The structures were fabricated as gold stripes embedded in CYTOP claddings with the fluidic channels defined via etching. The two multichannel structures are enabled using either a triple coupler or a corporate feed in cascade with an array of sensing waveguides. We demonstrate bulk and protein sensing for each channel comparable in performance to a single straight waveguide biosensor. Multiple channels are useful for parallel sensing, referencing, and common noise rejection.